Dynamical characteristics and influencing factors of stator end-windings of a turbine generator analyzed via heterogeneous element fusion modeling - Ying Zhou; Qing-lei Zhang; Jian-guo Duan (Energy Reports, 2021)
The power output rating of a turbine generator is affected directly by efficient cooling, especially near the stator end-windings. However, modeling the coolant flow through the stator end-windings of a high-powered generator remains challenging because of the many parts with irregular geometries and the intricacy of the cooling flow paths.In order to study the dynamical characteristics of stator end-windings, the finite element modeling of the stator end-winding with beam element, shell element and solid element has been established based on the analysis of different types of structural components. Further, a large number of modal calculations under different considerations including modulus of elasticity, boundary condition, connection area, position and temperature have been carried out.The frequency of the elliptical mode at the turbo-generator end was 81.5 Hz, and that at the exciter end was 77.2 Hz. The errors from the test average were 1.62% and 3.34%, respectively. The results showed that the FEM of the TG stator end reflects the vibration of the actual prototype precisely. The laws of natural frequencies with respect to different circumferential spacer blocks, radial pressure plate, external boundary conditions, spring-plate connection area, positions of spacers between bars and temperature including have been clarified.The structure of the stator end is complex, and researches continue into its dynamic characteristics with much work remaining. (1) Some more complex factors such as preload will be added to the model, and the influence of multiple factors on the vibration characteristics have been analyzed. (2) When using multi-point binding constraints, setting of the pinball region has a significant impact on calculation results. There is currently no fixed conclusion on how to set a reasonable PINBALL area size. (3) The mechanical properties of the end insulating material will change with the increase of temperature, but the trends cannot be predicted accurately.